Prodromal and Early bvFTD: Evaluating Clinical Features and Current Biomarkers - Katisko, Kasper; Cajanus, Antti; Korhonen, Titta; Remes, Anne M.; Haapasalo, Annakaisa; Solje, Eino (Frontiers in Neuroscience, 2019)
Despite the current diagnostic criteria, early diagnostics of behavioral variant of frontotemporal dementia (bvFTD) has remained challenging. Patients with bvFTD often present with misleading psychiatric phenotype, and, on the other hand, impairment in memory functions have increasingly been reported. However, impaired episodic memory is currently considered as an exclusion criterion for bvFTD. Single biofluid-based or imaging biomarkers do not currently provide sufficient sensitivity or specificity for early bvFTD diagnosis at single-subject level, although studies have suggested improved accuracy with different biomarker combinations. In this mini-review, we evaluate the core clinical features of early bvFTD and summarize the most potential imaging and fluid biomarkers for bvFTD diagnostics.